2018
DOI: 10.1016/j.bbr.2017.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Using c-Jun to identify fear extinction learning-specific patterns of neural activity that are affected by single prolonged stress

Abstract: Neural circuits via which stress leads to disruptions in fear extinction is often explored in animal stress models. Using the single prolonged stress (SPS) model of post traumatic stress disorder and the immediate early gene (IEG) c-Fos as a measure of neural activity, we previously identified patterns of neural activity through which SPS disrupts extinction retention. However, none of these stress effects were specific to fear or extinction learning and memory. C-Jun is another IEG that is sometimes regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 81 publications
3
18
0
Order By: Relevance
“…Exposure to reminder cues of aversive/traumatic situations reliably altered c-fos expression in stress circuitry regions [41][42][43] . Unexpectedly, when exposed to SPSassociated cues, resilient rats, which behaved as did control rats, were those showing the highest levels of c-fos expression in both the PL and the BLA.…”
Section: Emotional Remodeling With Oxytocin and C-fos Expressionmentioning
confidence: 97%
See 1 more Smart Citation
“…Exposure to reminder cues of aversive/traumatic situations reliably altered c-fos expression in stress circuitry regions [41][42][43] . Unexpectedly, when exposed to SPSassociated cues, resilient rats, which behaved as did control rats, were those showing the highest levels of c-fos expression in both the PL and the BLA.…”
Section: Emotional Remodeling With Oxytocin and C-fos Expressionmentioning
confidence: 97%
“…Indeed, hypo-activation of the mPFC has been extensively reported in PTSD patients and animal models [48][49][50][51][52] , whereas hypo-activation of the BLA is very discrepant with the main stream of the literature 53 . However, protocols ranging from script-driven imagery in PTSD patients 54 or exposure to cat odor 41 or SPS in rats 43 , have shown that the amygdala is not systematically activated upon re-exposure of vulnerable subjects to trauma-related cues. Second, consistent with our findings, a decrease in cfos expression has been detected in the BLA of vulnerable rats exposed to the traumatic experience with reminders of stress (TERS) model, which, as with our protocol, includes multiple exposures to stress cues 44 .…”
Section: Emotional Remodeling With Oxytocin and C-fos Expressionmentioning
confidence: 99%
“…These include the ventrolateral periaqueductal gray (vlPAG), which when inhibited impairs extinction (and fear learning) (Arico et al 2017 ; Tovote et al 2015 ), the BNST, inhibition of which prevents stress-induced fear renewal (Goode et al 2015 ) and the lateral part of the central amygdala (CeL), wherein different populations of cells are predicted to promote or oppose the expression of extinction via inputs from the paraventricular nucleus of the thalamus (PVT) (Do-Monte et al 2015 ; Haubensak et al 2010 ; Knobloch et al 2012 ; Li et al 2013 ; Penzo et al 2015 ). Thus, functional deficits at any of these multiple nodes within the highly integrated “extinction network” potentially contribute to extinction deficits (Knox et al 2018 ) (reviewed in Holmes and Singewald 2013 ) and enhanced propensity for fear relapse (Marek et al 2018 ) in psychiatric disorders due to irregularities in communication across the network. A recurring observation across a diverse set of models (Table 1 ) links functional deficiencies in certain nodes in the “extinction circuit;” in particular, emphasizing loss of function in the vmPFC (infralimbic cortex) and BLA and CeL subregions of the amygdala, and a corresponding over-engagement of the dmPFC (prelimbic cortex) CeM amygdala nucleus.…”
Section: Toward a Neurotopography Of Extinction: System And Circuit Mmentioning
confidence: 99%
“…Using animal model of PTSD, a few studies found that 5-HT2C ( Harada et al, 2008 ), Rin1 and Stathmin ( Han et al, 2017 ), beta-adrenoreceptors ( Ronzoni et al, 2016 ), Neuropeptide S ( Cohen et al, 2018 ), and beta-arrestin-2 ( Ding et al, 2017 ) may be implicated in PTSD associated behaviors. Recently, through using c-Fos or other markers of neuronal activity, increased activation of the amygdala was found to be associated with traumatic stress-induced behavioral changes, such as anxiety-like behaviors and deficit in fear extinction ( Muigg et al, 2008 ; Hoffman et al, 2014 ; Ritov et al, 2014 ; Yu et al, 2015 ; Knox et al, 2018 ). However, the temporal (early versus late phase after stress) and neuron-subtype (excitatory versus inhibitory activity) changes after traumatic stress are still unknown.…”
Section: Introductionmentioning
confidence: 99%